State Regulated Relationships: Mothers' Experiences of Partner Incarceration - Fields, Hannah Brianne (2019)
The effects of incarceration on families have been studied in-depth, but little research evaluates the effects on women parenting children after the incarceration of their romantic partner. This research evaluates how mothers manage to keep their families intact throughout the duration of their partner’s incarceration. I approached this question using a geography theory of care developed by Sophie Bowlby and Linda McKie. This theory states that the quality of care is dependent on the space in which it is provided, the social expectations within the caring environment, and the amount of time required to provide or receive care. Using this theoretical framework, I investigated how these mothers manage to care for their incarcerated partners, children, and themselves throughout their partner’s incarceration. To answer this question, I conducted nine in-depth, qualitative interviews with women experiencing partner incarceration across the state of Montana. Findings suggest that these women provide care for their partners, children, and self through visiting and sharing phone calls with their incarcerated loved ones. However, they also face significant barriers to providing this care, such as prison regulations and the financial cost of maintaining contact with incarcerated people. While I expected women to navigate these barriers by utilizing resources within their communities, I actually found that these women receive little support from their communities, and instead develop their own strategies for navigating barriers to providing and receiving care. This research uncovers the common barriers mothers in Montana confront when attempting to provide care for their families during partner incarceration. Eliminating these barriers has the potential to encourage family unity and, according to prior research, reduce an incarcerated person’s risk of recidivism